Subclinical encephalopathy in chronic obstructive pulmonary disease Encefalopatia subclínica na doença pulmonar obstrutiva crônica - Olga Maria Pinto de Lima; Ricardo de Oliveira-Souza; Omar da Rosa Santos; Pedro Araújo de Moraes; Leonardo Fontenelle de Sá; Osvaldo J.M. Nascimento (Arquivos de Neuro-Psiquiatria)
BACKGROUND: Clinical and experimental evidence suggests that chronic obstructive pulmonary disease (COPD) is associated with a variety of mental symptoms that range from cognitive slowing to mental confusion and dementia. PURPOSE: To test the hypothesis that COPD leads to cognitive impairment in the absence of acute confusion or dementia. METHOD: The global cognitive status of 30 patients with COPD without dementia or acute confusion and 34 controls was assessed with a Brazilian version of the Mini-Mental State Exam (MMSE). RESULTS: The MMSE scores were significantly lower in the patient group and inversely related to the severity of COPD. This finding could not be attributed to age, education, gender, daytime sleepiness, hypoxemia, chronic tobacco use, or associated diseases such as diabetes, depression, high blood pressure or alcoholism. CONCLUSION: These results suggest the existence of a subclinical encephalopathy of COPD characterized by a subtle impairment of global cognitive ability. CONTEXTO: Evidências clínicas e experimentais sugerem que a doença pulmonar obstrutiva crônica (DPOC) se associa a sintomas neurocomportamentais que variam da lentidão cognitiva à confusão mental e à demência. PROPÓSITO: Testar a hipótese de que a DPOC pode comprometer a cognição na ausência de estado confusional agudo ou de demência. MÉTODO: O estado cognitivo global de 30 pacientes com DPOC sem demência e sem confusão mental aguda e o de 34 controles foi examinado com a versão brasileira do Mini-Exame do Estado Mental (MEEM). RESULTADOS: As pontuações no meem mostraram-se significativamente mais baixas nos pacientes, e inversamente relacionadas à gravidade da DPOC. Este achado não pôde ser atribuído a diferenças de idade, escolaridade, sonolência diurna, hypoxemia, tabagismo crônico, ou a doenças associadas como diabetes, depressão, hipertensão arterial ou alcoolismo. CONCLUSÃO: Estes resultados sugerem a existência de uma encefalopatia subclínica da DPOC caracterizada por comprometimento sutil da capacidade cognitiva global.